PENGEMBANGAN LKPD BERBASIS MODEL CONCRETE REPRESENTATIONAL ABSTRACT (CRA) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS 2 SEKOLAH DASAR - Sofia Desti Anggraini; Fatkur Rohman; Fatonah, Pebriyanti; Nurhanurawati; Aprilia Nursanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The critical mathematical thinking ability of elementary school students in Indonesia remains relatively low, as reflected in the results of PISA and ANBK 2022. This is due to instruction that still focuses on rote memorization and the use of learning media that are not yet effective in developing conceptual understanding. This study aims to develop a Student Worksheet (LKPD) based on the Concrete Representational Abstract (CRA) model that is valid, practical, and effective in improving the critical mathematical thinking skills of second-grade elementary students on multiplication material. The research method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, and evaluation. Validation was conducted by experts in content, media, and language using the Gregory scale, while practicality was assessed through teacher response questionnaires. The results showed that the CRA-based LKPD met the criteria for high validity and received positive responses from teachers, categorized as